PROJECT DELAY PREDICTION WITH EARNED VALUE METHOD: A CASE ON THE CSS-APARTMENT PROJECT IN SURABAYA-INDONESIA - Arman Jayady; Robin Supratman (International Journal Labs, 2022)
The risk of delay is very likely to occur in a construction project. Especially in large-scale infrastructure projects that are accompanied by high complexity. Careful planning and prediction both related to aspects of design, implementation, including scheduling are very important. Problems that often arise in large-scale and complex construction projects are early predictions related to delays in the final completion of a project. This study aims to predict the occurrence of delays in project completion. Based on secondary data obtained from construction contractors and by using appropriate analytical procedures, the result is that the CSS-Apartment project is predicted to experience a delay of 57 weeks from the planned 146 weeks. The data is obtained directly from the project site. After all the data has been obtained, the processing is carried out using the Earned Value Method. Literature study is done by reading literature related to this writing Based on the case of an apartment project called CSS-Apartment Project in Surabaya - Indonesia, and using the Earned Value method.